PERAN PEREMPUAN DALAM PENCEGAHAN RADIKALISME - Musyafak, Najahan (Jurnal Dakwah, 2020)
This paper focuses on the women’s role in either domestic or public domain in preventing radicalism. A series of accidents with radical extremism background had happened in many places of Indonesia, such as suicide bombings, shootings and destruction of public facilities, which disrupted public security and government activities. This phenomenon is overshadowed by fear and insecurity threatening people's lives including women. Therefore, it need an appropriate response from related parties including women to anticipate the problems. Women is one of the potential parties who has a strategic role in order to prevent spreading of violence extremism. There is limited study that concern to the involvement of women in preventing violent extremism. This study tries to delineates women’s role of Solo areas to overcome of their problems in coping with fear, uncertainty, and social anxiety,  and negative impact of media coverage after many cases hit their territories.This study employs qualitative approach by interviewing women from various social, educational and religious backgrounds. They are prominent women’s organizations leaders namely Muslimat, PKK, Aisyiah, Religious extensionist, Islamic Party, Lecturers, Priest and Senior High School teachers  Data was collected through focus group discussions involving 11 informants from 4 districts namely Solo, Sukoharjo, Sragen and Karanganyar regencies. Informants were selected based on purposive sampling technique. The result of the study uncovers that the women have had a preparedness in preventing radicalism. It could be understood from their cognitive, affective and skill aspects. They had a good understanding of radical movement characteristics, sufficient assessment, and readynes to act in countering radical behavior